항응고제 복용 환자에서 족관절 관절경을 시행한 후 발생한 가성동맥류: 증례 보고 - 배정연; 강석웅; 신원철; 이상민; 우승훈; Jung Yun Bae; Suk-Woong Kang; Won Chul Shin; Sang-Min Lee; Seung Hun Woo (대한족부족관절학회지, 2025)
An anterior tibial artery pseudoaneurysm is a very rare complication after ankle arthroscopy using standard anteromedial and anterolateral portals. This paper reports the case of a 34-year-old male on anticoagulant (apixaban) treatment due to hypertrophic cardiomyopathy who underwent arthroscopic debridement 3 months earlier for acute gout arthritis of the ankle. The patient had sustained pulsatile, painful swelling of the anterior ankle after an arthroscopic procedure. Magnetic resonance imaging showed a pseudoaneurysm of the left anterior tibial artery at the ankle joint. The patient underwent surgical intervention, including evacuation of the pseudoaneurysm and hematoma.